Health career exploration through science, technology, engineering, and mathematics pipeline programming - Brew, Ranelle L.; Pokorski, Emily; Scheidel, Tess; Scherf, Brian; Agee, Kathy; DeJong, Pamela (Frontiers in Education, 2022)
Developing effective programs that aim to generate student interest in the pursuit of a career in health care is vital to avoid shortages among the workforce. As the American population ages, the country will continue to experience a higher demand for health care-trained individuals and services. Exposing racially diverse students to career options and the educational requirements early can serve as a pipeline for increasing interest in obtaining careers in health care professions overall. Program formatting resembles “summer camps” as it provides students with educational opportunities outside of the typical school curriculum. These programs have been an effective method of increasing interest because they can provide hands-on exposure to health care careers, an opportunity to job shadow, and tour local healthcare facilities. Programs aim to fill the gaps and increase interest in healthcare careers for underrepresented minority students. The literature identifies a few exploration camps across the United States, each with a data collection method unique to the program. This study examines the impact a summer health exploration camp can have on student efficacy and the effectiveness of generating student interest, in diverse populations, in the pursuit of a health-related career.